INFERRING NITRATE SOURCES THROUGH END MEMBER MIXING ANALYSIS IN AN INTERMITTENT MEDITERRANEAN STREAM - Bernal S.; Butturini A.; Sabater F. (My University, 2006)
We monitored 24 storms during the period 1998–2002 in order to elucidate whether the origin of nitrate could be inferred from water sources in the catchment. The study was performed in the Fuirosos catchment (10.5 km2) drained by an intermittent stream. Water sources were estimated through end member mixing analysis (EMMA) using chloride, sulfate and dissolved organic carbon as tracers. Three end members were identified in the catchment: event water, hillslope groundwater and riparian groundwater. Streamwater data encompassed the mixing space defined by the end members only during the 12 storms occurred during the wet period (from December to May). Water sources were related to stream nitrate concentrations during 6 of the 12 storms indicating a linkage between hydrological and nitrate sources. However, there was not a consistent pattern of a particular end member being a source of nitrate. EMMA was used to determine expected nitrate concentrations in stream water based on conservative mixing of the different water sources. The effect of the near- and in- stream zones on stream nitrate was inferred by comparing predicted nitrate concentrations to measured stream nitrate concentration. At discharges below 80 l s−1 stream nitrate concentrations were lower than expected from catchment sources in 82% of the cases suggesting nitrate retention in the near stream zones. The trend was the opposite at higher discharges.
Keywords: EMMA; INTERMITTENT STREAM; MEDITERRANEAN REGIONS; NITRATE SOURCES; STREAMWATER NITRATE; STORMFLOW GENERATION